The global stability of an SIRS model with infection age - Yuming Chen; Junyuan Yang; Fengqin Zhang (Mathematical Biosciences and Engineering)
Infection age is an important factor affecting the transmission ofinfectious diseases. In this paper, we consider an SIRS modelwith infection age, which is described by a mixed system ofordinary differential equations and partial differentialequations. The expression of the basic reproduction number$\mathscr {R}_0$ is obtained. If $\mathscr{R}_0\le 1$ then themodel only has the disease-free equilibrium, while if$\mathscr{R}_0>1$ then besides the disease-free equilibrium themodel also has an endemic equilibrium. Moreover, if$\mathscr{R}_0<1 then="" the="" disease-free="" equilibrium="" is="" globally="" asymptotically="" stable="" otherwise="" it="" is="" unstable="" if="" mathscr="" r="" _0="">1$ then the endemicequilibrium is globally asymptotically stable under additional conditions. The local stabilityis established through linearization. The global stability of thedisease-free equilibrium is shown by applying the fluctuationlemma and that of the endemic equilibrium is proved by employing Lyapunov functionals. The theoretical results are illustrated with numerical simulations.